2018
DOI: 10.1016/j.repc.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Importance of three-dimensional speckle tracking in the assessment of left atrial and ventricular dysfunction in patients with myotonic dystrophy type 1

Abstract: LA and LV global longitudinal strain is significantly decreased in patients with DM1, which may be an early marker of subclinical dysfunction in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Twenty-four studies assessed the cardiac muscle strength indirectly [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][104][105][106]112,113].…”
Section: Cardiac Muscle Strengthmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-four studies assessed the cardiac muscle strength indirectly [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][104][105][106]112,113].…”
Section: Cardiac Muscle Strengthmentioning
confidence: 99%
“…Twenty-two studies used echocardiography [34][35][36][37][39][40][41][42][43][44][45][46][47][48][49][50][51][52]105,106,112,113] and three used cardiac magnetic resonance [38,104,106] for the indirect evaluation of cardiac muscle strength. Main findings of the measures used to assess cardiac muscle strength for each study can be found in table 1 and Figure 2A.…”
Section: Cardiac Muscle Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac dysfunction is the second common cause of death, about 30% of mortality in adults with DM1. Cardiac involvement in DM1 includes conduction disease, atrial and ventricular tachyarrhythmias, atrioventricular block, left-ventricular systolic dysfunction, and myocardial fibrosis resulting in sudden death (Table 1) [31][32][33].…”
Section: Physiological and Systemic Features Of Dm1mentioning
confidence: 99%
“…3D‐STE can also detect early left ventricular dysfunction caused by hypertrophic cardiomyopathy, essential hypertension, type 2 diabetes mellitus, and chemotherapy drugs . In addition to evaluating LV myocardial motion, 3D‐STE can also evaluate the left atrium, right atrium, and right ventricle …”
Section: D‐ste In Assessing Myocardial Motionmentioning
confidence: 99%